Combined toll-like receptor 3/7/9 deficiency on host cells results in T-cell-dependent control of tumour growth - Johanna C. Klein (Nature Portfolio, 2017)
Activation of Toll-like receptor (TLR) is generally associated with increased immune activity. Here, the authors show, using syngeneic mouse models, that combined deficiency of TLR 3/7/9 in the host induces an inflamed tumour phenotype and results in T cell dependent tumour regression after an initial growth.